2008
DOI: 10.1186/1471-2105-9-544
|View full text |Cite
|
Sign up to set email alerts
|

AnEnPi: identification and annotation of analogous enzymes

Abstract: Background: Enzymes are responsible for the catalysis of the biochemical reactions in metabolic pathways. Analogous enzymes are able to catalyze the same reactions, but they present no significant sequence similarity at the primary level, and possibly different tertiary structures as well. They are thought to have arisen as the result of independent evolutionary events. A detailed study of analogous enzymes may reveal new catalytic mechanisms, add information about the origin and evolution of biochemical pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…In the years elapsed since our 1998 analysis, several studies explored various groups of alternative enzymes catalyzing the same biochemical reaction, including those belonging to the same protein (super)families [13,14]. Here, we focus on enzyme variants that possess (or could be inferred to possess) different structural folds and therefore appear to be evolutionarily unrelated (bona fide NISE).…”
Section: Introductionmentioning
confidence: 99%
“…In the years elapsed since our 1998 analysis, several studies explored various groups of alternative enzymes catalyzing the same biochemical reaction, including those belonging to the same protein (super)families [13,14]. Here, we focus on enzyme variants that possess (or could be inferred to possess) different structural folds and therefore appear to be evolutionarily unrelated (bona fide NISE).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, by combining sequence similarity with other functional features such as interacting partners, Espadaler et al [7] have shown that the protein sequences with sequence similarity are more likely to exhibit the same enzymatic activity if they share the same interacting partners. Otto et al [16] and Galperin et al [17] have developed methods for identification of analogous enzymes using sequence similarity by grouping proteins that share the same enzymatic activity (EC classes).…”
Section: Methods By Feature Spacementioning
confidence: 99%
“…Several studies have suggested that convergent evolution is also widespread [5,20,21] and that some non-homologous enzymes share structurally and functionally equivalent active site residues and similar mechanisms [20,22]. Recently, a quantitative assessment of convergently evolved enzymes revealed that of those enzymes that have similar overall reactions one third also had similar catalytic mechanisms [23••], concluding that functional analogs, like homologs, often share common mechanistic aspects along their reaction pathways.…”
Section: Lessons Learned From Studying the Evolution Of Enzyme Functionsmentioning
confidence: 99%